Low-value plant fiber material recombined fireproof door core and preparation method thereof
Through the multi-layer cross-composite technology of low-value plant fiber materials and inorganic flame retardant adhesive layers, the existing fire-resistant door core materials have been solved, and high fire-resistant and environmentally friendly fire-resistant door core products have been achieved.
Patent Information
- Application Number
- CN202411812153.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
The existing fireproof door core materials have poor physical and chemical properties, are fragile, and are prone to environmental pollution during production, resulting in a low pass rate of fireproof performance and cannot meet the requirements of high-quality development.
Low-value plant fiber materials are used for recombination, and combined with the inorganic flame retardant rubber layer through multi-layer cross-composite technology to form a heat-insulating refractory layer to prevent the direct combustion of the fiber veneer by flames, and a carbonized layer is formed at a high temperature to improve the refractory level.
It has achieved a fire-resistant door core with high fire resistance, impact resistance and strong deformation resistance. At the same time, due to the use of environmentally friendly materials, the production process has no emissions of harmful substances, which is in line with national industrial policies.
Smart Images

Figure CN119610304A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fireproof materials, and in particular to a fireproof door core reconstituted from low-value plant fiber materials and a preparation method thereof. Background Art
[0002] Fire doors are an important building fire separation facility. They can meet the requirements of fire resistance stability, integrity and thermal insulation within a certain period of time. They are mainly used to isolate fire sources, prevent the spread of fire and smoke, slow down the spread of fire, and provide escape opportunities for personnel evacuation. They are widely used in building passages, emergency exits, computer rooms, fire partitions and other places.
[0003] At present, the materials used in the core of fire doors are all organically synthesized magnesium phosphate cement, calcium silicate board, etc. The materials have poor physical and chemical properties and are fragile. The production and application processes are prone to produce harmful substances and environmental pollution. The fire performance qualification rate of the fire door products produced is low, which does not meet the requirements of high-quality development. Summary of the invention
[0004] The present invention provides a fireproof door core reconstituted with a low-value plant fiber material and a preparation method thereof. Pollution-free and environmentally friendly plant fibers are used as the fireproof door core material. The internal structure of the board core is highly homogeneous, stable and strong, and the door core has a good fireproof effect.
[0005] In order to solve the above technical problems, one of the purposes of the present invention is to provide a low-value plant fiber material reconstructed fireproof door core, comprising a plurality of laminated composite single boards, an inorganic flame retardant adhesive layer is arranged between two adjacent single boards and on the surface of the single board located on the outside, the number of the single boards is greater than or equal to 2, and the single board is a fine wood single board or a plant fiber single board;
[0006] The inorganic flame retardant adhesive layer is formed by an inorganic flame retardant adhesive, and the inorganic flame retardant adhesive includes the following components by weight: 3-4 parts of trisodium phosphate; 50-95 parts of magnesium chloride solution; 30-100 parts of starch glue; 1-3 parts of boric acid; 105-118 parts of magnesium oxide; 5-10 parts of silicon dioxide; 0.3-2 parts of tartaric acid; and 0.1-1 parts of emulsifier.
[0007] The mass fraction of the magnesium chloride solution is 52wt%-56wt%.
[0008] By adopting the above scheme, the present application uses inorganic flame retardant adhesive and veneer for multi-layer cross-compounding to form a heat-insulating fire-resistant layer between the plates. When the flame begins to burn, the inorganic flame retardant adhesive layer on the surface can effectively block the flame from directly burning the fiber veneer. The plate is carbonized under high temperature to form a carbonized layer. When the first layer of fiber veneer is completely carbonized under high temperature, the second layer of flame retardant adhesive plays the same flame retardant role, so that the fire door core reaches a higher fire resistance level, and has high strength, high impact resistance and deformation resistance, and is stable and strong. In addition, the present application uses a single board of fiber material, which can be recycled and reused for low-value plant fiber or waste materials, is low-carbon and environmentally friendly, has a light material density, has excellent sound insulation and heat insulation effects, and has no formaldehyde added in the production process, no harmful substances or harmful gas emissions, and complies with national industrial policies.
[0009] As a preferred embodiment, the plant fiber veneer is prepared by mixing the fiber material and the inorganic flame retardant adhesive in a mass ratio of 10:(1-3) and then flattening and cold pressing the mixture. The pressing pressure is 12-15 kg / cm 2 , the holding time is 24-36 hours.
[0010] As a preferred embodiment, the fiber material is at least one of bark, branches and leaves, straw, orange stalks, and reeds, and the particle length is ≤5mm.
[0011] As a preferred embodiment, the fiber material includes bark, straw, orange stalks and reeds in a mass ratio of 1:1:1:1.
[0012] As a preferred embodiment, the starch glue is prepared by mixing starch and water in a mass ratio of (0.2-0.5):1 and heating and gelatinizing.
[0013] As a preferred solution, the thickness of the single board is 5-20 mm, and the thickness of the inorganic flame retardant adhesive layer is 1-1.5 mm.
[0014] As a preferred solution, the fine wood veneer is made by sawing wood scraps into fine square materials and coating the inorganic flame retardant adhesive on the surface and then laying it flat and cold pressing it. The coating amount is 200-250g / m 2 , the pressing pressure is 12-15kg / cm 2 , the holding time is 24-36 hours.
[0015] As a preferred embodiment, the emulsifier is fatty alcohol polyoxyethylene ether.
[0016] As a preferred solution, the upper and lower surfaces of the fireproof door core are compounded with flame retardant panels, and the thickness of the flame retardant panels is 5-10 mm.
[0017] In order to solve the above technical problems, the second object of the present invention is to provide a method for preparing a fire door core reconstructed from low-value plant fiber materials, comprising the following steps:
[0018] A plurality of veneers are stacked and cold-pressed, and the inorganic flame retardant adhesive is applied between two veneers and on the surface of the outer veneer. After pressing, an inorganic flame retardant adhesive layer with a thickness of 0.8-1.5 mm is formed between the two veneers and on the surface of the outer veneer. After cutting, a fireproof door core is obtained.
[0019] As a preferred embodiment, the method for preparing the inorganic flame retardant adhesive comprises the following steps:
[0020] (1) Mix starch and water, heat to 70-80° C. for gelatinization, and cool to room temperature to obtain starch glue;
[0021] (2) stirring and mixing trisodium phosphate, magnesium chloride solution, emulsifier and starch glue to obtain a semi-finished product;
[0022] (3) Add tartaric acid, boric acid, magnesium oxide and silicon dioxide to the semi-finished product and mix them evenly to obtain a finished product. The viscosity of the inorganic flame retardant adhesive is 1500-2000cp.
[0023] As a preferred solution, the cold pressing pressure is 12-15 kg / cm 2 , the holding time is 24-36 hours.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. This application uses inorganic flame retardant adhesives and veneers for multi-layer cross-compounding to form a heat-insulating fire-resistant layer between the boards. The surface inorganic flame retardant adhesive layer can effectively block the direct burning of the fiber veneer by the flame. After the board is carbonized at high temperature to form a carbonized layer, the second layer of flame retardant adhesive plays the same barrier and flame retardant role, so that the fire door core reaches a higher fire resistance level, and the door core has high impact resistance and deformation resistance, and is stable and strong.
[0026] 2. This application uses a single board made of fiber material, which can be recycled from low-value plant fiber or waste materials. It is low-carbon and environmentally friendly, has a light material density, and has excellent sound insulation and heat insulation effects. No formaldehyde is added during the production process, and no harmful substances or harmful gases are emitted, which complies with national industrial policies. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 : It is a cross-sectional view of the fireproof door core reconstructed from low-value plant fiber materials of Examples 1-2 of the present invention (Note, left - Example 2, right - Example 1);
[0028] Figure 2 : The front of the door core during the fire resistance integrity test of the fire-resistant door core reconstructed with low-value plant fiber materials in Example 1 of the present invention (Note: left - fire resistance integrity test for 36 seconds; right - fire resistance integrity test for 1 hour, 10 minutes and 9 seconds);
[0029] Figure 3 : The back side of the door core during the fire resistance integrity test of the fire door core reconstructed from low-value plant fiber materials in Example 1 of the present invention (Note: left - fire resistance integrity test for 1 hour and 12 minutes; right - fire resistance integrity test for 1 hour and 14 minutes);
[0030] Figure 4 : The front and back of the composite door core after the fire-resistant integrity test was carried out according to the American standard UL10B / 10C after the low-value plant fiber material recombined fire-resistant door core composite flame-retardant board of Example 1 of the present invention (Note: left - the front of the composite door core after the fire-resistant integrity test for 2 hours and 25 seconds; middle - the back of the composite door core after the fire-resistant integrity test for 2 hours and 1 minute; right - the back of the composite door core after the fire-resistant integrity test for 2 hours and 4 minutes);
[0031] Figure 5 : This is the certification certificate of the fire-proof door core made of low-value plant fiber material in Example 1 of the present invention, which has passed the American standard UL10B / 10C after being composited with a flame-retardant board. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0036] As used herein:
[0037] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0038] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0039] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically inventing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is invented separately. For example, when a range of "1 to 5" is invented, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0040] In these examples, parts and percentages are by mass unless otherwise indicated.
[0041] "Parts by mass" refers to the basic unit of measurement that represents the proportional relationship between the masses of multiple components. 1 part can represent any unit mass. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Or, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts.
[0042] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0043] In the description of the present invention, it is necessary to understand that the terms "up", "down", "left", "right", "top", "bottom", etc., indicating directions or positional relationships, are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the present invention.
[0044] In order to further illustrate the present invention, the low-value plant fiber material reconstituted fireproof door core and the preparation method thereof provided by the present invention are described in detail in combination with the examples below, but they should not be construed as limiting the scope of protection of the present invention. Unless otherwise specified, the raw materials used can be obtained from the market, and the same raw materials are used in parallel experiments.
[0045] Preparation Example 1
[0046] An inorganic flame retardant adhesive comprises 3kg of trisodium phosphate, 75kg of magnesium chloride solution, 70kg of starch glue, 2kg of boric acid, 112kg of magnesium oxide, 8kg of silicon dioxide, 0.86kg of tartaric acid and 0.32kg of OS-15 emulsifier (fatty alcohol polyoxyethylene ether), wherein the mass concentration of the magnesium chloride solution is 50%; the starch glue is prepared by heating and gelatinizing starch and water in a mass ratio of 0.4:1; the specific preparation method comprises the following steps:
[0047] (1) Starch and water are heated to 75° C. in a mass ratio of 0.4:1, and then cooled to room temperature to obtain starch glue;
[0048] (2) stirring and mixing trisodium phosphate, magnesium chloride solution, OS-15 emulsifier and starch glue to obtain a semi-finished product;
[0049] (3) Add tartaric acid, boric acid, magnesium oxide and silicon dioxide to the semi-finished product and mix well to obtain a finished product with a viscosity of 1800 cp.
[0050] Comparative Preparation Example 1
[0051] An inorganic flame retardant adhesive comprises 3kg of trisodium phosphate, 75kg of magnesium chloride solution, 70kg of starch glue, 2kg of boric acid, 80kg of magnesium oxide, 0.86kg of tartaric acid and 0.32kg of OS-15 emulsifier (fatty alcohol polyoxyethylene ether), wherein the mass concentration of the magnesium chloride solution is 50%; the starch glue is prepared by heating and gelatinizing starch and water in a mass ratio of 0.4:1; the specific preparation method comprises the following steps:
[0052] (1) Starch and water are heated to 75° C. in a mass ratio of 0.4:1, and then cooled to room temperature to obtain starch glue;
[0053] (2) stirring and mixing trisodium phosphate, magnesium chloride solution, OS-15 emulsifier and starch glue to obtain a semi-finished product;
[0054] (3) Add tartaric acid, boric acid and magnesium oxide to the semi-finished product and mix well to obtain a finished product with a viscosity of 1800 cp.
[0055] Example 1
[0056] A method for preparing a fireproof door core reconstituted from low-value plant fiber materials comprises the following steps:
[0057] (1) crushing plant fibers of tree bark, rice straw, orange stalk and reed, wherein the length of the crushed particles is ≤5 mm, and then mixing the bark, rice straw, orange stalk and reed in a ratio of 1:1:1:1 by weight to form a fiber material;
[0058] (2) The fiber material and the inorganic flame retardant adhesive of Preparation Example 1 were stirred and mixed evenly in a mass ratio of 10:2, and then laid flat and pressed into a plant fiber single board at a pressing pressure of 13 kg / cm 2 , the holding time is 30 hours, and the thickness of the single board is 15mm;
[0059] (3) After the single board is made, three single boards are stacked and cold-pressed according to the application of structural mechanics, symmetry and verticality. The inorganic flame retardant adhesive of Preparation Example 1 is applied between the two single boards and on the surface of the outer single board. After pressing, an inorganic flame retardant adhesive layer with a thickness of about 1 mm is formed between the two single boards and on the surface of the outer single board to extend the overall fire resistance time of the door core. The pressing pressure is 13 kg / cm 2 The pressure holding time is 30 hours. After cutting, the fireproof door core is obtained.
[0060] Example 2
[0061] A method for preparing a fireproof door core reconstituted from low-value plant fiber materials comprises the following steps:
[0062] (1) Cut the wood scraps into thin square pieces with a thickness of 10 mm to ensure uniform thickness;
[0063] (2) The surface of the fine material is coated with the inorganic flame retardant adhesive of Preparation Example 1, with a coating amount of 250 g / m 2 , multiple fine square materials are laid flat and cold pressed into fine wood veneer, the pressing pressure is 13kg / cm 2 , the holding time is 30 hours, and the thickness of the fine wood veneer is 15mm;
[0064] (3) After the single board is made, three single boards are stacked and cold-pressed according to the application of structural mechanics, symmetry and verticality. The inorganic flame retardant adhesive of Preparation Example 1 is applied between the two single boards and on the surface of the outer single board. After pressing, an inorganic flame retardant adhesive layer with a thickness of about 1 mm is formed between the two single boards and on the surface of the outer single board to extend the overall fire resistance time of the door core. The pressing pressure is 13 kg / cm 2 The pressure holding time is 30 hours. After cutting, the fireproof door core is obtained.
[0065] Comparative Example 1
[0066] A method for preparing a fireproof door core reconstituted from low-value plant fiber materials comprises the following steps:
[0067] (1) crushing plant fibers of tree bark, rice straw, orange stalk and reed, wherein the length of the crushed particles is ≤5 mm, and then mixing the bark, rice straw, orange stalk and reed in a ratio of 1:1:1:1 by weight to form a fiber material;
[0068] (2) The fiber material and the inorganic flame retardant adhesive of Preparation Example 1 were stirred and mixed evenly in a mass ratio of 10:2, and then laid flat and pressed into a plant fiber single board at a pressing pressure of 13 kg / cm 2 , the holding time is 30 hours, and the thickness of the single board is 45mm;
[0069] (3) After the veneer is made, the inorganic flame retardant adhesive of Preparation Example 1 is coated on the outer surface of the veneer, and an inorganic flame retardant adhesive layer with a thickness of about 1 mm is formed on the surface of the veneer after pressing. The pressing pressure is 13 kg / cm 2 The pressure holding time is 30 hours. After cutting, the fireproof door core is obtained.
[0070] Comparative Example 2
[0071] A method for preparing a fireproof door core reconstituted from low-value plant fiber materials comprises the following steps:
[0072] (1) Cut the wood scraps into thin square pieces with a thickness of 10 mm to ensure uniform thickness;
[0073] (2) The surface of the fine material is coated with the inorganic flame retardant adhesive of Preparation Example 1, with a coating amount of 250 g / m 2 , multiple fine square materials are laid flat and cold pressed into fine wood veneer, the pressing pressure is 13kg / cm 2 , the holding time is 30 hours, and the thickness of the fine wood veneer is 45mm;
[0074] (3) After the veneer is made, the inorganic flame retardant adhesive of Preparation Example 1 is coated on the surface of the veneer, and an inorganic flame retardant adhesive layer with a thickness of about 1 mm is formed on the surface of the veneer after pressing. The pressing pressure is 13 kg / cm 2The pressure holding time is 30 hours. After cutting, the fireproof door core is obtained.
[0075] Comparative Example 3
[0076] A method for preparing a fireproof door core comprises the following steps:
[0077] (1) crushing plant fibers of tree bark, rice straw, orange stalk and reed, wherein the length of the crushed particles is ≤5 mm, and then mixing the bark, rice straw, orange stalk and reed in a ratio of 1:1:1:1 by weight to form a fiber material;
[0078] (2) The fiber material and the inorganic flame retardant adhesive of Preparation Example 1 were stirred and mixed evenly in a mass ratio of 10:2, and then laid flat and pressed into a plant fiber single board at a pressing pressure of 13 kg / cm 2 , the holding time is 30 hours, and the thickness of the single board is 15mm;
[0079] (3) After the veneer is made, three veneers are stacked and cold pressed according to the application of structural mechanics, symmetry and verticality. OAK-BOND white latex OAK-370 is applied between two adjacent veneers with a coating amount of 250g / m 2 , the pressing pressure is 13kg / cm 2 The pressure holding time is 30 hours. After cutting, the fireproof door core is obtained.
[0080] Comparative Example 4
[0081] A method for preparing a fireproof door core comprises the following steps:
[0082] (1) Cut the wood scraps into thin square pieces with a thickness of 10 mm to ensure uniform thickness;
[0083] (2) The surface of the fine material is coated with the inorganic flame retardant adhesive of Preparation Example 1, with a coating amount of 250 g / m 2 , multiple fine square materials are laid flat and cold pressed into fine wood veneer, the pressing pressure is 13kg / cm 2 , the holding time is 30 hours, and the thickness of the fine wood veneer is 15mm;
[0084] (3) After the single board is made, three single boards are stacked and cold pressed according to the application of structural mechanics, symmetry and verticality. The inorganic flame retardant adhesive of Preparation Example 1 is applied between two adjacent single boards and on the surface of the outer single board. After pressing, OAK-BOND white latex OAK-370 is applied between the two single boards, and the coating amount is 250g / m 2 , the pressing pressure is 13kg / cm 2 The pressure holding time is 30 hours. After cutting, the fireproof door core is obtained.
[0085] Comparative Example 5
[0086] A method for preparing a fireproof door core, wherein each step and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the inorganic flame retardant adhesive of Preparation Example 1 is replaced by an equal amount of the inorganic flame retardant adhesive of Comparative Preparation Example 1.
[0087] Comparative Example 6
[0088] A method for preparing a fireproof door core, wherein each step and the reagents, equipment, and process parameters used in each step are the same as those in Example 2, except that the inorganic flame retardant adhesive of Preparation Example 1 is replaced by an equal amount of the inorganic flame retardant adhesive of Comparative Preparation Example 1.
[0089] Performance testing
[0090] 1. The fire resistance integrity test of the fire door cores of the embodiment and the comparative example was carried out in accordance with GB 12955-2008 and GB / T 7633-2008. The test results are as follows: Figure 2-3 And as shown in Table 1.
[0091] 2. The fire resistance and thermal insulation properties of the fireproof door cores of the embodiment and the comparative example were tested in accordance with GB 12955-2008 and GB / T 7633-2008. The test results are shown in Table 1.
[0092] 3. After the high-temperature combustion test, according to GB 12955-2008 standard, a high-pressure water gun was used to impact the fire door of Example 1-2. There was no water leakage or cracking, and the airtightness of the door leaf and the door frame met the requirements.
[0093] 4. Apply the inorganic flame retardant adhesive of Preparation Example 1 to the upper and lower surfaces of the fire door core of Example 1, with a coating amount of 250g / m 2 , and add composite 8.5mm flame retardant board, cold press for 10 hours, pressure 13Kg / m 2 , and then the composite door core was tested according to the American standard UL10B / 10C. The results are as follows Figure 4 As shown in the figure, after the 2-hour fire resistance test, no through cracks occurred in the composite door core. The obtained certification is as follows Figure 5 shown.
[0094] Table 1 - Performance test results of fire door cores of examples and comparative examples
[0095]
[0096]
[0097] like Figure 2-3As shown, during the fire resistance test of the fire door core reconstructed with low-value plant materials in Example 1, it was found within 1.17 hours that the third layer of board on the back-to-fire side was not completely carbonized, and there were no through cracks and holes. However, at 1.23 hours, significantly larger through holes were found in the fire door core, indicating that the third layer of board was severely carbonized and the fire resistance began to decline.
[0098] like Figure 4 As shown, the low-value plant material recombined fireproof door core of the present invention can be based on this and add a flame retardant board below to increase the thickness of the composite door core to further extend the fire resistance time to 2 hours. Figure 5 The composite door core has passed the American standard UL10B / 10C standard test and certification.
[0099] As shown in Table 1, compared with Comparative Examples 1-6, the present application uses low-value plant fibers and waste wood fiber to prepare veneer materials, which has the advantages of low carbon and environmental protection. The inorganic flame retardant adhesive layer is bonded to the veneer, and the layers are cross-compounded. After the cold pressing process, the inorganic flame retardant adhesive penetrates into the wood fiber guide holes on the surface of the board, and the bonding force and flame retardant performance between the boards are enhanced. The fire-resistant door core is compounded with three layers of veneer. When the flame starts to burn, the inorganic flame retardant adhesive on the surface effectively blocks the flame from directly burning the fiber board. The board is carbonized under high temperature to form a carbonized layer. When the first layer of fiberboard is carbonized under high temperature, the second layer of inorganic flame retardant adhesive plays the same role, improving the flame retardant and heat insulation effect, so that the overall fire resistance level of the door core is higher. Among them, the inorganic flame retardant adhesive in Comparative Examples 5-6 is not added with silicon dioxide, and the magnesium oxide content is lower than that in Example 1, resulting in a decrease in the fire resistance of the fire door core, insufficient flame retardant and heat insulation capacity, and a decrease in the fire resistance level of the fire door core.
[0100] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A fireproof door core made of low-value plant fiber material, characterized in that: It comprises a plurality of laminated and composite single boards, an inorganic flame retardant adhesive layer is provided between two adjacent single boards and on the surface of the single board located outside, the number of the single boards is greater than or equal to 2, and the single boards are fine wood single boards or plant fiber single boards; The inorganic flame retardant adhesive layer is formed by an inorganic flame retardant adhesive, and the inorganic flame retardant adhesive includes the following components by weight: 3-4 parts of trisodium phosphate; 50-95 parts of magnesium chloride solution; 30-100 parts of starch glue; 1-3 parts of boric acid; 105-118 parts of magnesium oxide; and 5-10 parts of silicon dioxide. Tartaric acid: 0.3-2 parts; emulsifier: 0.1-1 parts; The mass fraction of the magnesium chloride solution is 52wt%-56wt%.
2. The low-value plant fiber material reconstructed fireproof door core according to claim 1, characterized in that: The plant fiber veneer is prepared by mixing the fiber material and the inorganic flame retardant adhesive in a mass ratio of 10:(1-3) and then flattening and cold pressing the mixture. The pressing pressure is 12-15 kg / cm 2 , the holding time is 24-36 hours.
3. The low-value plant fiber material reconstructed fireproof door core according to claim 2, characterized in that: The fiber material is at least one of tree bark, branches and leaves, straw, orange stalks, and reeds, and the particle length is ≤5mm.
4. The low-value plant fiber material reconstructed fireproof door core according to claim 3, characterized in that: The fiber material includes tree bark, rice straw, orange stalk and reed in a mass ratio of 1:1:1:1; the starch glue is prepared by mixing starch and water in a mass ratio of (0.2-0.5):1 and heating and gelatinizing; and the emulsifier is fatty alcohol polyoxyethylene ether.
5. The low-value plant fiber material reconstructed fireproof door core according to claim 1, characterized in that: The thickness of the single board is 5-20 mm, and the thickness of the inorganic flame retardant adhesive layer is 1-1.5 mm.
6. The low-value plant fiber material reconstructed fireproof door core according to claim 1, characterized in that: The fine wood veneer is made by sawing wood scraps into fine square materials and coating the inorganic flame retardant adhesive on the surface and then laying it flat and cold pressing it. The coating amount is 200-250g / m 2 , pressing pressure is 12-15kg / cm 2 , the holding time is 24-36 hours.
7. The low-value plant fiber material reconstructed fireproof door core as claimed in claim 1, characterized in that: The upper and lower surfaces of the fireproof door core are compounded with flame retardant panels, and the thickness of the flame retardant panels is 5-10 mm.
8. A method for preparing a fireproof door core made of low-value plant fiber materials as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: A plurality of veneers are stacked and cold-pressed, and the inorganic flame retardant adhesive is applied between two veneers and on the surface of the outer veneer. After pressing, an inorganic flame retardant adhesive layer with a thickness of 0.8-1.5 mm is formed between the two veneers and on the surface of the outer veneer. After cutting, a fireproof door core is obtained.
9. The method for preparing a fireproof door core reconstituted from low-value plant fiber materials as claimed in claim 8, characterized in that: The preparation method of the inorganic flame retardant adhesive comprises the following steps: (1) Mix starch and water, heat to 70-80° C. for gelatinization, and cool to room temperature to obtain starch glue; (2) stirring and mixing trisodium phosphate, magnesium chloride solution, emulsifier and starch glue to obtain a semi-finished product; (3) Add tartaric acid, boric acid, magnesium oxide and silicon dioxide to the semi-finished product and mix them evenly to obtain a finished product. The viscosity of the inorganic flame retardant adhesive is 1500-2000cp.
10. The method for preparing a fireproof door core reconstituted from low-value plant fiber materials according to claim 8, characterized in that: Cold pressing pressure is 12-15kg / cm 2 , the holding time is 24-36 hours.
Citation Information
Patent Citations
Novel plant fiber flame retardant adhesive and preparation method thereof
CN108949061A
Adhesive as well as preparation method and application thereof
CN115029082A
Heat preservation and insulation fireproof door and production process thereof
CN115139594A
Annueine analogs, salts, compositions and methods of use
CN117177959A
Potch processing compound, processing apparatus and method for processing silver coloured camera
CN1407400A
Cited By
Biomass fiber-containing non-combustible fireproof base material, integrated fireproof door core and preparation method of biomass fiber-containing non-combustible fireproof base material and integrated fireproof door core
CN122403834A